Will enterprise social networking systems promote knowledge management and organizational learning? An empirical study. Issue 1 (2nd January 2018) - Qi, Cong; Chau, Patrick Y. K
ABSTRACT: Nowadays, enterprise social media practitioners and researchers are keen to know how the enterprise usage of social media can be converted into the improved organizational performance. Meanwhile, organizational learning has long been considered as one of the measures of organizational performance. This article investigated the impact of enterprise social networking systems (ESNS) usage on knowledge management processes and organizational learning; in particular, we examined the mediating role of knowledge creation and knowledge sharing. Four theories from sociology and strategic management were used to build the hypotheses in the research model. An online survey was conducted to empirically test the model. Our study results showed that ESNS usage directly and indirectly influences organizational learning; and that knowledge management processes (knowledge creation and sharing) mediate the path between the two. This study contributes to the existing literature on enterprise social media for three reasons. First, it is among the first to connect the three independent concepts (social media, knowledge management, and organizational learning) and explore their relationships in one theoretical framework. Second, this work also specifically examines the influence of ESNS (Yammer in this case) on organizational processes and outcomes. Third, this is a pioneering study that employs multiple theories to address the research questions under the organizational social media context. Therefore, the research gives implications for both practitioners and scholars who are interested in understanding the effectiveness of ESNS usage in the modern organizations today.